Використання об'єктів інтелектуальної власності на підприємстві як засіб економічного зростання - Полозова, Т. В.; Безлєпкін, Л. С. (ХНУРЕ, 2015)
Intellectual property rights play an important role in the development of the enterprise. Implementation and use of objects of intellectual property and other intangible assets can increase the market value of the company. Usage of intellectual property rights is fundamental to the economic growth of the enterprise and the economy in general in today’s world.
Keywords: інтелектуальна власність; об'єкт інтелектуальної власності; інтелектуальне виробництво